MULTILEVEL INFORMATION SYSTEM FOR RECORDING THE STUDENTS ACADEMIC PERFORMANCE IN THE CUMULATIVE ASSESSMENT SYSTEM - Aloshyn , Serhii; Piatykop, Olena; Fedosova , Irina (Journal of Information Technologies in Education (ITE), 2022)
The COVID-19 pandemic has had a major impact on education. All over the world, educational institutions have been forced to switch to distance learning. Due to the current situation, the demand for online education and information resources to support it has grown all over the world. The issue of not only the organization of online learning, but also the processes of electronic assessment of student progress is relevant. The authors analyzed business processes in assessing students’ knowledge and existing software. The main disadvantage of the existing systems of support of the educational process at the university is the limited, and sometimes inability, access to them for certain participants in the educational process, especially in the conditions of distance learning. It is determined that a system with functional capabilities is needed for the following actors: student, teacher, head of department, dean and dean’s office. The data in the system must be stored in a database, and the interface for accessing them must be possible from any web browser. The work is devoted to the development of such software. The developed system has the architecture of a distributed three-tier information system with access to the database, and consists of the following main links, such as: a web server with developed software as an application server, a database server running MySQL DBMS, a web browser as a client software. The use of a success assessment system provides many advantages, including: improving the quality of information processing, speeding up work processes and increasing the availability of data for all participants in the educational process. The COVID-19 crisis and unprecedented disruptions in the education system are far from over. Thus, the growing demand for online learning tools and related resources will remain in demand. Therefore, the developed multilevel information system for accounting for student performance is relevant now. This software will also be useful in the traditional form of learning. Because keeping an e-journal will reduce the filling of paper documents, reduce the burden on the teacher and provide easy access to information of other participants in the educational process: students and staff of the dean’s office.